2013
DOI: 10.1093/infdis/jit495
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 22 Inhibits Intracellular Growth of Mycobacterium tuberculosis by Enhancing Calgranulin A Expression

Abstract: Previously, we found that interleukin 22 (IL-22) inhibits intracellular growth of Mycobacterium tuberculosis in human monocyte-derived macrophages (MDMs). In the current study, we determined the mechanisms underlying these effects. We found that W7, a phagolysosomal fusion inhibitor, abrogates IL-22-dependent M. tuberculosis growth inhibition in MDMs, suggesting that IL-22 acts through enhanced phagolysosomal fusion. Our microarray analysis indicated that recombinant IL-22 (rIL-22) enhances the expression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 52 publications
0
59
0
Order By: Relevance
“…IL-22-producing cells at mucosal surfaces play a crucial role in the host innate defense against microorganisms, including M.tb (Aujla and Kolls, 2009). A recent report showed that IL-22 can inhibit the growth of M.tb in macrophages by enhancing phagolysosomal fusion (Dhiman et al, 2014). In addition, the IL-22-producing T cell-mediated immunity is important for the protective anti- M.tb response (Bhuju et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…IL-22-producing cells at mucosal surfaces play a crucial role in the host innate defense against microorganisms, including M.tb (Aujla and Kolls, 2009). A recent report showed that IL-22 can inhibit the growth of M.tb in macrophages by enhancing phagolysosomal fusion (Dhiman et al, 2014). In addition, the IL-22-producing T cell-mediated immunity is important for the protective anti- M.tb response (Bhuju et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In another side, S100A8/A9 (calprotectin) was discovered as an immunogenic protein expressed by neutrophils with potent anti‐microbial properties . Reports showed that IL‐22 inhibits intracellular growth of mycobacterium tuberculosis, and contributes to antimicrobial defense and restitution of colonic epithelial integrity during colitis by enhancing S100A8 expression . There is also accumulating evidence that S100A8/A9 not only act as biomarkers for numerous inflammatory diseases, but are also proposed as biomarkers for other cancers, such as prostate, breast and colorectal .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in non-human primate infected with Mtb, CD4 + T cells expressing membrane-bound IL-22 limit Mtb intracellular growth in macrophages (255). IL-22 can also inhibit intracellular growth of Mtb in human monocyte-derived macrophages by promoting phagolysosomal fusion and induction of Calgranulin A, a heterodimer of S100A8 and S100A9 proteins (256). Moreover, human NK cells cultured with Mtb-infected macrophages produce IL-22 and mediate macrophage activation (257).…”
Section: Cytokinesmentioning
confidence: 99%